Analisis Deskriptif Pola Minat Kejuruan Pada Berbagai Paket Keahlian Di Sekolah Menengah Kejuruan - FARIDA, RAHAYU, Prof. Kumaidi, P.Hh.D (2017)
The result of the descriptive analysis shows that there is no change of the interest typhology that was arranged based on the data of this research compared with previous interest typhology. The aim of this research is to do the descriptive analysis to the patterns of student's interest in vocational school. Interest typhology descriptive analysis is arranged base on the data from the student that had finished their education in vocational school. The result of the descriptive analysis shows that there is no change of the interest typhology that arranged based on the data of this research compared with the previous interest typhology. Another finding of this research is the male subjects tend into type R (Realistic) were female subjects are into type C (conventional), and this is in accordance with the results of research in various parts of the world. The research also found there are 35% contained dominant expertise package preferred by male students and 40% expertise packages dominant preferred by female student, anda 25% expertise packages in preferred by both males and females. Other findings are samples in Indonesia generally have a typology of interest S (Social) and E (Entrepreneur) on the entire expertise packages group membership, and not appearing at all the type I (Investigative). The conclution of the study is the typhologi of interest from 36 expertise packages in the the past study can be standart of expertise packages's interest typhologi. Keywords: vocational, interests, typology